2001
DOI: 10.1111/j.1749-6632.2001.tb03944.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD36, the Macrophage Class B Scavenger Receptor, in Atherosclerosis

Abstract: Recent work in the field of atherosclerosis has greatly expanded our knowledge of the pathogenesis of this disease. Scavenger receptors, including CD36, are thought to be most important early in the disease progression during macrophage uptake of modified LDL and foam cell formation. Genetically engineered murine models have been used to elucidate the contribution of the different scavenger receptors, to identify specific ligands related to LDL modifications, and to assess the possible therapeutic ramification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 45 publications
3
76
0
1
Order By: Relevance
“…5,6,32 The findings in the current study that showed that freshly isolated DKO peritoneal macrophages exhibited decreased neutral lipid staining, decreased CD36 mRNA levels and that the DKO mice had decreased atherosclerosis are consistent with these previous studies. However, additional studies will be necessary as the link between CD36 expression and atherosclerosis has recently been challenged by Moore et al; these authors reported that Cd36 Ϫ/Ϫ Apoe Ϫ/Ϫ mice exhibited increased aortic sinus lesions, even though the DKO peritoneal macrophages exhibited reduced lipid accumulation in vitro.…”
Section: Discussionsupporting
confidence: 80%
“…5,6,32 The findings in the current study that showed that freshly isolated DKO peritoneal macrophages exhibited decreased neutral lipid staining, decreased CD36 mRNA levels and that the DKO mice had decreased atherosclerosis are consistent with these previous studies. However, additional studies will be necessary as the link between CD36 expression and atherosclerosis has recently been challenged by Moore et al; these authors reported that Cd36 Ϫ/Ϫ Apoe Ϫ/Ϫ mice exhibited increased aortic sinus lesions, even though the DKO peritoneal macrophages exhibited reduced lipid accumulation in vitro.…”
Section: Discussionsupporting
confidence: 80%
“…Besides being a FA transporter, CD36 acts as scavenger receptor, the major receptor for oxLDL in macrophages [30]. Furthermore, CD36 has been previously demonstrated to internalize oxLDL in adipocytes, suggesting that they can function as phagocytes, like macrophages, and that might participate in the clearance of circulating oxLDL [10].…”
Section: Discussionmentioning
confidence: 99%
“…MΦ uptake of OxLDL provides ligands for PPARγ, including 9-HODE and 13-HODE [46,171]. The mechanism by which OxLDL upregulates CD36 appears to involve activation of PPARγ [172] and PPARα [173]. PPARγ is induced in human monocytes following exposure to OxLDL and is expressed at high levels in foam cells [48].…”
Section: Interrelationship Between Eicosanoids Ppars and Stimulationmentioning
confidence: 99%